The effect of water deficiency stress and foliar application of indole acetic acid at different stages of grain growth on grain yield and germination traits of produced seeds in bread wheat cultivars - مجید عبدلی; محسن سعیدی; ماندانا آژند; سعید جلالی-هنرمند (علوم و فناوری بذر ایران, 2014)
Plant growth regulators are the main factors in grain yield formation However, their physiological roles have not been fully identified. On the other hand, water stress is the main factor in reducing grain yield and germination characteristics. To this end, two experiments were carried out in the research farm and laboratory of Campus of Agriculture and Natural Resources of Razi University in Iran during 2010-2011 and 2011-2012 years in a split-plot factorial arranged in a randomized complete blocks design with three replications. The irrigation treatments including non water stress and water deficiency stress (from anthesis and continued until physiological maturity). The wheat cultivars including Pishtaz, Marvdasht, DN-11and 336 and the foliar application of indole acetic acid (dose of 50 μM)treatments including control, used at the beginning of grain growth (from anthesis) and at the beginning of grain filling (from 14 days after anthesis) at the entire plants. Under non water stress, the grain yield of Marvdasht was greater than other cultivars. More yield reduction of this Marvdasht in water deficiency compared to other cultivars showed more sensitivity of this cultivar to post-anthesis water deficiency and DN-11 in this situation had the lowest grain yield reduction. Foliar application of indole acetic acid (IAA) at the beginning of grain growth caused the most increase in grain yield. In this situation, IAA caused more increase in the grain yield of Marvdasht cultivar. But, this treatment at the beginning of grain filling did not have such effect. Seeds were obtained from the field were studied in the view of germination and seedling growth characteristics in the laboratory and the result showed that, plumule length and germination percentage were not affected by post-anthesis water deficiency. Under post-anthesis water deficiency, Plumule to radicle ratio and germination rate significantly increased and other parameters showed a significant decrease. Mean comparison of foliar application of IAA at the beginning of grain filling showed that this significantly increased germination characteristics. With respect to these results, Auxin may via positive effects on seed quality and not quantity (seed weight) may be had positive effects on seed germination characteristics.